Non-psychogenic polydipsia in 45-year-old man with primary hyperparathyroidism and recurrent bilateral nephrolithiasis (Faculty of Medicine Universitas Indonesia, 2012)
Non-psychogenic polydipsia with hyponatremia is a rare clinical presentation. Primary hyperparathyroidism is a disorder of calcium, phosphate, and bone metabolism caused by increased level of parathyroid hormone (PTH). It is estimated the incidence of primary hyperparathyroidism are 21.6 per 100,000 person a year. This case report describe a 45-year-old man presented with non-psychogenic polydipsia. This patient drank a lot of water out of the fear of recurrent kidney stones. He had history of recurrent nephrolithiasis with hypercalcemia. We investigate further the cause of hypercalcemia and we diagnosed primary hyperparathryoidism as the cause. (Med J Indones. 2012;21:230-4)